A comparative study of functioning and non-functioning pituitary adenomas. Issue 14 (9th April 2021) - Qin, Jiayin; Li, Kai; Wang, Xijuan; Bao, Yongzhen
Abstract : Abstract: Pituitary tumors commonly cause visual impairment and the degree of impairment can depend on the size, location, and type of the tumor. However, no studies have been made regarding the differences caused by functioning pituitary adenoma (FPA) and non-functioning pituitary adenoma (NFPA). We aimed to investigate the relationship between clinical characteristics and visual impairment in patients with FPA and NFPA. This case series study included 73 pituitary adenoma patients. All patients underwent ophthalmic evaluations, and we retrospectively reviewed their medical records. Tumor types were confirmed by histological analysis, and the tumor volume was calculated. Magnetic resonance imaging was used to determine the tumor diameter. The observation indices of the two groups were compared. The correlation between the visual field and tumor volume was analysed using scatter plots. We enrolled 30 patients in the FPA group and 43 in the NFPA group. The first symptoms presented in the eyes in 23% of FPA patients and 41.9% of NFPA patients. The best-corrected visual acuity of the FPA group was better than that of the NFPA group, and 34 (56.7%) and 73 (84.9%) eyes in these groups had visual field defects, respectively. The visual field defects of the FPA patients were lighter than those of the NFPA patients. Except for the anteroposterior diameter, there were no differences in the other parameters of tumor diameter between the groups. The tumor volume of the FPA group was smaller than that of the NFPA group. The tumor size was positively correlated with the mean deviation and negatively correlated with the mean sensitivity in both groups. There was a longer delay between the onset of signs and symptoms and treatment in the FPA group than in the NFPA group. Future studies should focus on visual field defects caused by FPA and NFPA.